First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Improving long-term storage of liquid-preserved bovine semen: Effect of extender, cooling protocol and holding temperature on sperm quality and fertility - M.L. Neubert; S. Henneberg; A. Riedel; Y. Schulze; M. Hürland; J.H. Osmers; C. Wesenauer; M. Jung; Á.C. Bajcsy; M. Schulze (Theriogenology, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Exploring the Ecology of Deep-Sea Hydrothermal Vents in a Metacommunity Framework - Lauren S. Mullineaux; Anna Metaxas; Stace E. Beaulieu; Monika Bright; Sabine Gollner; Benjamin M. Grupe; Santiago Herrera; Julie B. Kellner; Lisa A. Levin; Satoshi Mitarai; Michael G. Neubert; Andreas M. Thurnherr; et al. (Frontiers in Marine Science, 2018)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study - Rogier B. Mars; Sean Foxley; Lennart Verhagen; Saad Jbabdi; Jérôme Sallet; MaryAnn P. Noonan; Franz-Xaver Neubert; Jesper L. Andersson; Paula L. Croxson; Robin I. M. Dunbar; Alexandre A. Khrapitchev; Nicola R. Sibson; et al. (Brain Structure and Function, 2016)

Prevalence of antibodies against hepatitis A virus among children and adolescents in Germany - A. Krumbholz; A. Neubert; H. Girschick; H. I. Huppertz; P. Kaiser; J. Liese; A. Streng; T. Niehues; J. Peters; A. Sauerbrey; H. Schroten; T. Tenenbaum; et al. (Medical Microbiology and Immunology, 2013)

A Novel Approach for In Vitro Studies Applying Electrical Fields to Cell Cultures by Transformer-Like Coupling - R. Hess; H. Neubert; A. Seifert; S. Bierbaum; D. A. Hart; D. Scharnweber (Cell Biochemistry and Biophysics, 2012)

Modulation of short intra-cortical inhibition during action reprogramming - Franz-Xaver Neubert; Rogier B. Mars; Etienne Olivier; Matthew F. S. Rushworth (Experimental Brain Research, 2011)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)

Penetration Profile of Taurine in the Human Skin and Its Distribution in Skin Layers - D. L. P. da Silva; S. B. Thiago; F. A. Pessôa; Y. Mrestani; H. H. Rüttinger; J. Wohlrab; R. H. H. Neubert (Pharmaceutical Research, 2008)

Fatty acid interdigitation in stratum corneum model membranes: a neutron diffraction study - A. Ruettinger; M. A. Kiselev; Th. Hauss; S. Dante; A. M. Balagurov; R. H. H. Neubert (European Biophysics Journal, 2008)

Recent Results from Studies of Electric Discharges in the Mesosphere - T. Neubert; M. Rycroft; T. Farges; E. Blanc; O. Chanrion; E. Arnone; A. Odzimek; N. Arnold; C.-F. Enell; E. Turunen; T. Bösinger; Á. Mika; et al. (Surveys in Geophysics, 2008)

Ectomycorrhiza communities of red oak (Quercus rubra L.) of different age in the Lusatian lignite mining district, East Germany - S. Gebhardt; K. Neubert; J. Wöllecke; B. Münzenberger; R. F. Hüttl (Mycorrhiza, 2007)

Effects of turbulence‐mediated larval behavior on larval supply and settlement in tidal currents - Heidi L. Fuchs; Michael G. Neubert; Lauren S. Mullineaux (Limnology and Oceanography, 2007)
Intertidal gastropod larvae retract their vela and sink in strong turbulence, and this behavior potentially increases settlement in turbulent coastal habitats. We incorporated turbulence‐induced sinking behavior of mud snail larvae ( Ilyanassa obsoleta ) in a vertical advection‐diffusion model to characterize behavioral effects on larval supply and settlement in a tidal channel. Throughout flood and ebb tides, larvae that sink in turbulence have higher near‐bed concentrations than passive larvae. This high supply of larvae enables behaving larvae to settle more successfully than passive larvae in strong currents characteristic of tidal inlets. Unlike passive larvae, those that sink in turbulence settle more successfully in stronger currents than in weaker ones and would concentrate their settlement in energetic tidal zones. Turbulence‐mediated behavior may give intertidal larvae a greater ability to select habitats and may reduce larval mortality rates due to settlement failure.

New insights into the structure and hydration of a stratum corneum lipid model membrane by neutron diffraction - M. A. Kiselev; N. Y. Ryabova; A. M. Balagurov; S. Dante; T. Hauss; J. Zbytovska; S. Wartewig; R. H. H. Neubert (European Biophysics Journal, 2005)

Identification of theta-class glutathione S-transferase in liver cytosol of the marmoset monkey - Thomas G. Schulz; Frederike A. Wiebel; Ricarda Thier; Diether Neubert; Donald S. Davis; Robert J. Edwards (Archives of Toxicology, 2000)

Body size and food web structure: testing the equiprobability assumption of the cascade model - M. G. Neubert; S. C. Blumenshine; D. E. Duplisea; T. Jonsson; B. Rashleigh (Oecologia, 2000)

Mixing Ratios and Photostationary State of NO and NO2 Observed During the POPCORN Field Campaign at a Rural Site in Germany - F. Rohrer; D. Brüning; E. S. Grobler; M. Weber; D. H. Ehhalt; R. Neubert; W. Schüßler; I. Levin (Journal of Atmospheric Chemistry, 1998)

Direct Determination of Drug Content in Semisolid Formulations Using Step-Scan FT-IR Photoacoustic Spectroscopy - R. Neubert; B. Collin; S. Wartewig (Pharmaceutical Research, 1997)

Influence of 13-cis and all- trans retinoic acid on rat embryonic development in vitro: correlation with isomerisation and drug transfer to the embryo - S. Klug; J. Creech Kraft; E. Wildi; H. -J. Merker; T. V. N. Persaud; H. Nau; D. Neubert (Archives of Toxicology, 1989)